Prevalence of goiter and iodine status among 6-12 years school age children in district Kohat, Pakistan - Subhan, Fazli; Jahangir, Muhammad; Saira, Saira; Khattak, Rehman Mehmood; Shahab, Muhammad; Haq, Matiul; Khattak, Muhammad Nasir Khan (South East Asia Journal of Public Health, 2015)
Pakistan is considered to be one of the most severely iodine deficient countries in the region. A decade earlier, 70% of the population was estimated to be at risk of iodine deficiency. However, the recent use of iodized salt has reduced the intensity of the problem. Earlier studies regarding iodine deficiency in Pakistan were restricted to the northern mountainous regions, but have now been extended to the sub-Himalaya areas and the plains of Punjab. The aim of the present study was to investigate the prevalence of goiter and iodine status among school children in district Kohat, Pakistan. The 30 cluster approach was adopted for the study. From each cluster, 40 samples were collected from school going children. The palpation method was used to measure goiter grade, whereas, for urinary iodine estimation, the wet digestion method was used. The prevalence of goiter in the district was found to be 35% (37.16% in boys and 33% in girls). The median urinary iodine concentration was found to be 56±31.19?g/L. Estimation of iodine content in salt illustrated that 56.8% people were consuming non-iodized salt and 43.5% were using iodized salt. The current study suggests a severe iodine deficiency in school children of district Kohat and regular iodine supplementation is required on an instant basis. South East Asia Journal of Public Health Vol.4(2) 2014: 42-46